Foliar Application of Ascorbic Acid and α-Tocopherol Enhances Salinity Tolerance in Hordeum vulgare L. by Regulating Antioxidant Enzymatic Activity and Improving Physiological and Biochemical Responses - Sadaf; Sami Ullah; Sikandar Shah; Aftab Jamal; Adil Mihoub; Muhammad Farhan Saeed; Iftikhar Ahmad; Emanuele Radicetti; Adil Zia; Andrea Mastinu; Jakub Černý (Journal of Crop Health, 2025)
Soil salinity severely impairs crop productivity by disrupting physiological and biochemical processes. This study investigated the efficacy of foliar-applied ascorbic acid (AsA) and α‑tocopherol (α-toc) in enhancing salinity tolerance in barley ( Hordeum vulgare L. cv. AJJ). A pot experiment using a randomized complete block design with three replicates was conducted under controlled conditions. Seedlings at the 4–5 leaf stage were exposed to 0, 40, or 80 mM NaCl salinity stress, followed by foliar treatments of AsA and α‑toc (150 mg L⁻ 1 ). Germination, agronomic, physiological, and biochemical parameters were analyzed. Salinity stress at 40 and 80 mM NaCl significantly reduced germination percentage (GP) by 18.6% and 18.4%, respectively, compared to the control (86.6%). Foliar application of AsA + α-toc under 40 and 80 mM stress restored GP to 82.3% and 81.7%, reflecting recoveries of 16.8% and 15.6% overstressed groups. Water content in leaves, shoots, and roots declined by 10–30% under salinity but improved by 15–25% with AsA + α-toc. Photosynthetic pigments were severely affected: chlorophyll a and total chlorophyll content (TCC) decreased by 45.7% (1.75 to 0.95 mg g⁻ 1 FW) and 10.9% (1.75 to 1.56 mg g⁻ 1 FW) at 40 and 80 mM NaCl, respectively. AsA + α-toc mitigated these losses, elevating TCC by 42.6% under 80 mM stress. Soluble protein content increased by 186% (0.50 to 1.43 mg g⁻ 1 ) under 80 mM stress but was stabilized by antioxidant treatments. Antioxidant enzymes, including superoxide dismutase (SOD) and peroxidase (POD), surged by 40–60% under salinity, while AsA + α-toc reduced hydrogen peroxide (H 2 O 2 ) and malondialdehyde (MDA) levels by 30–50%. The combined application of AsA and α‑toc proved most effective, enhancing stress tolerance through improved osmotic regulation, antioxidant defense, and chlorophyll preservation. These findings highlight the potential of AsA and α‑toc as sustainable agronomic tools for cultivating barley in saline soils, with AsA showing marginally greater efficacy. Further field studies are warranted to validate these results under different climatic conditions.